The Effect of Using Microencapsulation Product of Noni Fruit Extract (Morinda citrifolia L.) In Diet to Characteristics of Sentul Chicken Meat - Nusantara, Sekarupa Rengganis; Widjastuti, Tuti; Indrijani, Heni (Jurnal Produksi Ternak Terapan, 2025)
Sentul chicken is a local from Ciamis Regency that has potential as an alternative source of animal protein. The utilization of microencapsulated noni fruit extract products that are rich in bioactive compounds in the ration is expected to improve the quality of meat through improving the nutritional composition of the ration. This study was using 100 Sentul chickens divided into four treatment groups, where the rations were given with variations in the addition of microencapsulated products at doses of 0, 75, 150, and 225 mg/kg MNFE. The microencapsulation method was carried out by coating noni extract using maltodextrin and drying it using the spray drying method. The results showed that microencapsulation of noni fruit extract had a significant effect on carcass weight, cholesterol content, and fat content of chicken meat. The optimal doses was found at 75-150 mg/kg MNFE which resulted in an increase in carcass weight and a decrease in cholesterol levels and the most effective meat fat. Therefore, using of microencapsulated noni fruit extract not only improves meat quality, but can also be an alternative solution in the livestock industry, especially in reducing the use of Antibiotic Growth Promoter (AGP) and increasing poultry meat quality.